Uma análise de desempenho de funções de encriptação nativas de SGDBs Open Source - Rosa, Andre de Souza; Lazarin, Nilson M. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.233641, 2023)
Given the growing need for security in digital environments, global legislation has emerged to regulate, among other things, data storage. However, security measures impact system performance, causing greater slowdowns and resource consumption. This study evaluates the performance of encryption functions in three Open Source Database Management Systems, MariaDB, PostgreSQL and Firebird, with different workloads. Metrics such as average execution time, average CPU usage and average RAM consumption were considered. Taking into account the results obtained and the security provided by the supported operation modes, PostgreSQL is indicated as the best option.